Trans‐10 18:1 in ruminant meats: A review. Issue 6 (4th October 2021) - Alves, Susana P.; Vahmani, Payam; Mapiye, Cletos; McAllister, Tim A.; Bessa, Rui J. B.; Dugan, Michael E. R.
Abstract: Trans ( t ) fatty acids (TFA) from partially hydrogenated vegetable oils (i.e., industrial trans ) have been phased out of foods in many countries due to their promotion of cardiovascular disease. This leaves ruminant‐derived foods as the main source of TFA. Unlike industrial TFA where catalytic hydrogenation yields a broad distribution of isomers, ruminant TFA are enzymatically derived and can result in enrichment of specific isomers. Comparisons between industrial and ruminant TFA have often exonerated ruminant TFA due to their lack or at times positive effects on health. At extremes, however, ruminant‐sourced foods can have either high levels of t 10‐ or t 11‐18:1, and when considering enriched sources, t 10‐18:1 has properties similar to industrial TFA, whereas t 11‐18:1 can be converted to an isomer of conjugated linoleic acid ( cis ( c )9, t 11‐conjugated linoleic acid), both of which have potential positive health effects. Increased t 10‐18:1 in meat‐producing ruminants has not been associated with negative effects on live animal production or meat quality. As such, reducing t 10‐18:1 has not been of immediate concern to ruminant meat producers, as there have been no economic consequences for its enrichment; nevertheless at high levels, it can compromise the nutritional quality of beef and lamb. In anticipation that regulations regarding TFA may focus more on t 10‐18:1 in beef and lamb, the present review will cover its production, analysis, biological effects, strategies for manipulation, and regulatory policy.